Risk management of less lethal options : evaluation, deployment, aftermath, and forensics - Wyant, R.T.; Burns, Thomas (Police officer) (Boca Raton : CRC Press, Taylor & Francis Group, 2014)
'With risk management as the primary goal, this book helps law enforcement professionals reduce liability and increase safety to all parties involved when a less-lethal weapon is deployed to address an unruly individual or disrupt civil unrest. It covers testing, training, deployment, and forensics. The book addresses the pros and cons of each less lethal option along with preferred deployment protocols. It also addresses the future of these weapons and draws on the experiences of real incidents and participation on the board of the NIJ TWG for Less Lethal Weapons'--
'Introduction It all began with a TASER incident in 2001 that brought two cops, Chris Myers and Tom Burns, and a forensic scientist, Rick Wyant, together to help develop protocols to better investigate a class of weapons that were quickly gaining momentum and popularity. As our partnership grew, we realized all shared a similar desire to take a new approach to understanding less lethal weapons. Tom wanted to test the ordnance used during the WTO riots. Chris asked if we could catch stuff on fire with pepper spray. John Allgire joined in to help with all of the testing. After determining that our unique methodology to testing products yielded some interesting and eye-opening data, we formed CRT Less Lethal to help share our knowledge. Years later, when CSI and Mythbusters copied one of our experiments on their TV shows, we knew we were onto something special. Rick, Tom & John compiled this text as a culmination of that testing and lessons learned from investigating negative outcomes from all over the US and abroad. We realized that there were people being injured or dying, as well as large settlements in court cases, based on inaccurate knowledge or insufficient testing of less lethal options. We will not only discuss how these tools are deployed, but also outline ways a police department can apply simple concepts and techniques to manage risk and limit liability. These methods were developed over a decade of testing, training, evaluating, deploying, analyzing and testifying to related to the use of these tools. We were fortunate enough to have two icons in the less lethal realm to assist us in this venture. Steve Ijames launches the text with a brilliant and perceptive forward. Sid Heal keeps it going by sprinkling his wisdom and insight throughout the book's entirety'--
Includes bibliographical references and index.
Keywords: Law enforcement; Nonlethal weapons; Police; Firearms -- Law and legislation; Forensic sciences